Genotypic characterization, antimicrobial susceptibility and virulence determinants of Campylobacter jejuni and Campylobacter coli isolated from pastured poultry farms - Awad, Amal; Yeh, Hung-Yueh; Ramadan, Hazem; Rothrock, Michael J. (Frontiers in Microbiology, 2023)
Campylobacter is the leading bacterial pathogen causing foodborne illnesses worldwide. Pasture farming is regarded as an important source of agricultural production for small farming communities. Consumer preference for pasture-raised products has increased; however, there is a paucity information on the microbiological quality of these poultry products. The purpose of this study was to explore genetic relatedness of these isolates, to assess antibiotic resistance phenotypically and genotypically, and to screen the presence of virulence determinants of isolates from poultry farms from southeastern USA. Ninety-seven Campylobacter isolates previoudly identified by Q7 BAX® System Real-Time PCR were genotyped by MLST. Campylobacter isolates were then evaluated for their phenotypic antimicrobial susceptibility against nine antimicrobial agents using Sensititre plates. Additionally, Campylobacter isolates were tested for the presence of antimicrobial resistance-associated elements. Furthermore, Campylobacter isolates were screened for the presence of 13 genes encoding putative virulence factors by PCR. These included genes involved in motility, adhesion and colonization, toxin production and invasion. Among 97 Campylobacter isolates, C. jejuni (n=79) and C. coli (n=18) were identified. By MLST, C. jejuni isolates were assigned to seven clonal complexes. Among them, ST-353, ST-607 and ST-21 were the most common STs recognized. All C. coli (n=18) isolates were included in CC-828. Eight STs identified were not belonging any previous identified clonal complex. Campylobacter isolates displayed a high resistance against tetracycline (81.4%), while a low rate of resistance was observed against azithromycin and erythromycin, nalidixic acid, ciprofloxacin, gentamicin, telithromycin, florfenicol and clindamycin. Thirteen isolates (13.54%) were pan-susceptible to all tested antibiotics, while nine isolates were multi-antimicrobial resistant. Interestingly, there were no isolates resistant to all antimicrobial classes. Thr86Ile mutation was identified in all quinolones resistant strains. Erythromycin encoding gene (ermB) was identified in 75 % of erythromycin resistant isolates. The tetO gene was identified in 93.7% of tetracycline resistant isolates and six tetracycline susceptible isolates. In conclusion, the results revealed that Campylobacter isolates from pasture-raised poultry farms showed the ST relatedness to Campylobacter isolates commonly associated with humans, indicating pasture-raised broiler flocks, similar to conventionally-reared broiler flocks, as a potential vector for antibiotic-resistant and pathogenic strains of thermophilic Campylobacter to humans.